Visualized Real-Time Early Warning Technology for Safety Monitoring of Excavation Construction in Dense Housing Area of Urban Villages - TANG Xiaolin; ZHOU Yifan; ZHU Zhaoyin; ZHANG Zhongbing; SHEN Jiali; JIN Lianghai (Renmin Zhujiang)
The rain-sewage diversion project in the dense housing area of urban villages involves a large amount of trench excavation,which leads to prominent safety problems in construction.The safety monitoring and analysis of trench excavation are characterized by high requirements,complex data association,and poor data conditions,and thus we propose a theoretical method of organic integration of land subsidence mechanisms and data analysis process.The intelligent analysis method for land subsidence in trench excavation is based on digital twin technology,which integrates data and knowledge to realize visualized real-time monitoring,prediction,and control of land subsidence in urban villages.The method extracts and expresses the scenes,processes,objects,problems,and knowledge of the whole life cycle of land subsidence in survey and design,trial excavation,and formal excavation construction,and a big data analysis model of land subsidence based on data-knowledge fusion is developed.The research results can provide a scientific basis for the safety decision-making of excavation construction in the dense housing area of urban villages.